Web-based learning : what do we know? Where do we go? - Bruning, Roger H.; Horn, Christy A.; PytlikZillig, Lisa M. (Emerald Publishing Limited : Information Age Pub., 2003)
Topics covered in this volume include: research on web-based learning; ways to reduce cognitive load in multimedia learning; gathering and organizing web-based information; the risks in cyberspace; engineering perspectives; and the pedagogical impact of course management systems.